Alat Kontrol dan Monitor Pada Rumah Sederhana Berbasis Raspberry - Syarifuddin Kasim; Yunus Tjandi (Seminar Nasional LP2M UNM, 2019)
Many Accidents and detriment due to improper use and installation of control and monitor devices, especially in simple home and office. This study aims to produce Software, Control/Monitor, Interface and Raspberry-Based Applications to control and monitor the Electrical Devices of a Simple Home/Office, both at close range and remotely, with the help of an installed Router/Web Modem at the Board House so that it is economical in electricity usage. The results of the study show that the Raspberry-based Control and Monitor that are made are functioning properly, this is evidenced from the results of the research trials, in a Simple House, in the form of a Board House using a Smartphone.